2008
DOI: 10.1111/j.1748-8583.2008.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Careers and temporal flexibility in the new economy: an Anglo‐Dutch comparison of the organisation of consultancy work

Abstract: Knowledge workers are widely considered to represent the vanguards of a new employment era, characterised by a greater degree of balance in the relationship between the employer and the knowledge worker. This fundamental shift in power relations is expected to lead to the emergence of a new group of so‐called ‘free’ or empowered portfolio workers, who share boundaryless career arrangements and internationally ‘universal’ forms of flexibility. However, such propositions have been made without extensive comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
1
22
0
3
Order By: Relevance
“…Professionals and organizations need flexibility -not as a goal in itself, but as a means to secure work and income, whilst maintaining their market and competitive positions (Donnelly, 2008;Fenwick, 2007;Vaiman et al, 2011). Moreover, a growing number of organizations prefer to have a core of staff in fixed employment surrounded by a flexible shell of workers with temporary or project-based contracts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professionals and organizations need flexibility -not as a goal in itself, but as a means to secure work and income, whilst maintaining their market and competitive positions (Donnelly, 2008;Fenwick, 2007;Vaiman et al, 2011). Moreover, a growing number of organizations prefer to have a core of staff in fixed employment surrounded by a flexible shell of workers with temporary or project-based contracts.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a growing number of organizations prefer to have a core of staff in fixed employment surrounded by a flexible shell of workers with temporary or project-based contracts. It is expected that the work of organizations will be progressively more project-based and that IPs will play an increasingly important role in flexible shells (Donnelly, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Future research could expand upon this study to illuminate our understanding of the complexity of the organization of working time in different occupations and national economies. Such an understanding may provide an insight into the different ways in which the long working hours cultures in these occupations can be challenged and addressed (see, e.g Donnelly 2008…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, the literature on the organization and administration of working time has expanded, with increasing research into flexible working arrangements, trends observed among knowledge workers and national variations in working time (Altonji and Usui 2007; Donnelly 2008; Evans et al . 2004; Lee et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation